Fermented palm kernel cake improves the nutrient degradation of beef cattle by modulating the rumen microbiota - Mi, Hui; Wang, Zhaozhe; Xiao, Haixiang; Zhu, Jinjia; Hou, Pengxia; Zhou, Chuanshe; Xiao, Dingfu (Frontiers in Microbiology, 2025)
IntroductionThis study aimed to evaluate the effects of fermenting palm kernel cake (PKC) using Aspergillus niger and mannanase on its nutritional quality, and to assess the impact of replacing soybean meal and corn with fermented PKC (FPKC) on growth performance, rumen fermentation, nutrient digestibility, and rumen microbiota in beef cattle.MethodsPKC was co-fermented with Aspergillus niger and mannanase to enhance its nutritional profile. Thirty beef cattle were randomly assigned to two dietary groups (n = 15 per group): a control group (CON) receiving a conventional diet, and a treatment group (FP) fed a diet in which soybean meal and corn were partially substituted with FPKC. A 90-day feeding trial was conducted, during which body weight was monitored, and rumen fluid and fecal samples were collected on days 30, 60, and 90 to evaluate growth performance, rumen fermentation, and nutrient digestibility. On day 90, rumen samples were subjected to 16S rRNA gene sequencing to characterize the rumen microbial community composition.ResultsCo-fermentation significantly improved the nutritional quality of PKC and reduced its mannan content (P < 0.05). Although growth performance did not differ significantly between the FP and CON groups throughout the trial (P > 0.05), the FP group exhibited significantly higher digestibility of dry matter (DMD), crude protein (CPD), and neutral detergent fiber (NDFD) after 90 days compared to the CON group (P < 0.05). Rumen fermentation analysis revealed lower concentrations of butyrate and NH3-N in the FP group than in the CON group (P < 0.05), while other fermentation parameters showed no significant differences (P > 0.05). 16S rRNA sequencing indicated that the FP group had a higher relative abundance of Bacteroidetes, whereas Firmicutes were more prevalent in the CON group. The Rikenellaceae RC9 gut group was identified as a dominant genus in the FP group, while the CON group was characterized by higher abundances of Ruminococcus, Christensenellaceae R-7 group, and Butyrivibrio.ConclusionThese findings demonstrate that co-fermentation with Aspergillus niger and mannanase effectively enhances the nutritional value of PKC. The inclusion of FPKC in the diet improves nutrient digestibility and modulates rumen microbial composition in beef cattle, supporting its potential as a valuable alternative feed ingredient.